Influence of Pier Size on its Failure Mode under Near-Fault Vertical Earthquake. (4th October 2022) - Xia, Houzheng; An, Wenjun; Zhou, Lin
Abstract : To calculate the influence of pier size on the pier failure mode, a double-span continuous girder bridge model was selected for analysis. The transient wave function expansion method was used to calculate the excitation conditions required for pier separation and the limit solution of pier longitudinal deformation under pier separation, and the indirect mode superposition method was used to calculate the vertical impact force of the pier-beam. The calculation results show that the higher the pier height, the smaller the section size, the larger the vertical seismic acceleration required to separate the pier-beam, the smaller the vertical contact force of the pier-beam, and the larger the most unfavorable value of the longitudinal deformation of the pier caused by separation. The stress of the bridge pier before and after separation is compared and the influence of separation on the failure of the bridge pier is put forward. The study shows that when pier and beam separation occurs, there may be multiple failure modes superimposed on the pier, and the first failure mode will have variation with the change in pier size.